Formulation and evaluation of diclofenac sodium microemulsion transdermal spray for rheumatoid arthritis - Laiba Shahid; Samar Fatima Hashmi; Sibgha Basharat; Muhammad Ans Ali; Nimra Ikram; Hamza Zafar; Talib Hussain (AMMANIF, 2024)
Background: The growth of a topical vehicle microemulsions has been more enhanced compared to the normal skin applications such as creams, gels among others. These micro-structured vehicles showed enhanced solubilization of drug and improved skin permeation as compared to conventional topical systems. Objective: This study was aimed to formulate and evaluate the topical diclofenac sodium microemulsion spray claimed to be having better bioavailability, greater drug solubility, enhanced skin permeation, and lesser side effects. Method: Diclofenac sodium microemulsion was prepared by constructing pseudo ternary phase diagram followed by water titration method. The oil phase IPM 10%(v/v) was selected on the basis of drug solubility whereas the surfactant:cosurfactant mixture (tween80 : polyethylene glycol 400) 50%(v/v) was on the basis of their oil solubilization and efficiency to form ME from pseudo-ternary phase diagrams and then 40%(v/v) aqueous phase and 4%(w/v) drug was added. Results: This optimized micro emulsion spray was evaluated by some preliminary tests and confirmatory tests. Results of tests indicated that the formulation was optimized as it was transparent on visual inspection having 6.8 pH, 113nm droplet size, and 36.70cP viscosity. Dye solubility testing confirmed that micro emulsion was W/O. FTIR and DSC studies showed that micro emulsion was compatible with excipients. Drug content and release was more than 90%. The kinetics studies revealed that diclofenac sodium micro emulsion followed Korsmeyer Peppas Model, Higuchi Model, and first order kinetics. Conclusion: This study made a good effort to develop a unique drug delivery system that had increased drug solubility and skin penetration with lesser side effects.